How to redesign the fiscal regime of the eurozone: An alternative take on lessons from US and eurozone experiences - Jörg Bibow (European Trade Union Institute (ETUI), 2019)
This Working Paper examines options for the design of a workable fiscal union for the euro area. It provides a comparative study of fiscal institutions in the US and euro area in order to supply lessons from the operation of the US fiscal regime that could inform the design of the, hitherto dysfunctional, euro regime. The paper argues that common, rather than asymmetrical, shocks are the norm in the euro area and that the euro's institutions are seriously deficient in dealing with area-wide recession and systemic financial crises.
Keywords: 330; economic integration; European Integration; fiscal policy; euro zone; USA; Wirtschaftsintegration; Europäische Integration; Finanzpolitik; Eurozone; Vergleich; USA